Pesan-Pesan Dakwah Akun Instagram @Sahabat_Islami dalam Meningkatkan Kesadaran Keagamaan: (Studi Pada Mahasiswa Komunikasi dan Penyiaran Islam (KPI) Fakultas Dakwah dan Komunikasi UIN Ar-Raniry) - Lisa Seri Wahyuni (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This article examines the message of preaching in the Instagram media @sahabat_islami, because along with the development of the era, the netizens use Instagram media as a media in reviewing about the Islamic, with the media, the messages will be delivered quickly to the followers. This study uses a qualitative research type with a descriptive approach. It is used to examine the design as a whole, while the approach is a descriptive approach with the goal of being able to describe comprehensively the research results obtained in the field. The results of the discussion say that the messages of Da'wah through the media istagram @sahabat_islami contain the message of Aqidah, sharia message, and Akhlak. Netizen comments on the post are positive and negative. Positive comments are helpful for gaining insight into Keislaman, a negative comment saying that the account is indicated by the business. The message of preaching on the Instagram account @sahabat_islami in raising religious awareness is, since becoming an Instagram follower they have an impact in the better direction, and often practice about the knowledge gained through the postings on the account.